2011
DOI: 10.1002/ajmg.a.34152
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous C‐propeptide mutations in COL1A1: Osteogenesis imperfecta type IIC and dense bone variant

Abstract: Osteogenesis imperfecta type IIC (OI IIC) is a rare variant of lethal OI that has been considered to be an autosomal recessive trait. Twisted, slender long bones with dense metaphyseal margins and normal vertebral bodies in OI IIC contrast with crumpled, thick long bones and multiple vertebral compression fractures in OI IIA. Here, we report on two sporadic patients with classical OI IIC and a pair of siblings, with features of OI IIC but less distortion of the tubular bones (OI dense bone variant). One case w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…These individuals have a phenotype of mild OI with multiple fractures but without abnormal growth or major skeletal deformities. However, while individuals with OI usually have thin long bones with thin cortices and reduced bone mass, bone mass in some (though not all) of these individuals has been reported to be increased with thickened long bone cortices (9,(12)(13)(14)(15)(16). This appearance is similar to GDD, but the characteristic jaw lesions of GDD were not reported in these cases.…”
Section: Discussionmentioning
confidence: 93%
“…These individuals have a phenotype of mild OI with multiple fractures but without abnormal growth or major skeletal deformities. However, while individuals with OI usually have thin long bones with thin cortices and reduced bone mass, bone mass in some (though not all) of these individuals has been reported to be increased with thickened long bone cortices (9,(12)(13)(14)(15)(16). This appearance is similar to GDD, but the characteristic jaw lesions of GDD were not reported in these cases.…”
Section: Discussionmentioning
confidence: 93%
“…(Ala1387Val) located in the C‐propeptide region of COL1A1 . This particular mutation had been reported in one family with a recurrence of severe OI [Takagi et al, ]. He was also found to be heterozygous for a novel c.3278G>A, p.(Arg1093His) variant in the helical domain of COL1A1 .…”
Section: Resultsmentioning
confidence: 76%
“…Other phenotypes resulting from a C‐propeptide variant of COL1A1 include OI with dense bone disease—see below [Takagi et al, ] and gnathodiaphyseal dysplasia, which has previously been described as OI with “unusual skeletal features” [McInerney‐Leo et al, ]. Hence, there can be consistent phenotypic correlation for some OI‐causing variants, such as for the COL1A1 c.4237G>A; p.(Asp1413Asn) described in type II OI, but a lack of phenotypic correlation for others.…”
Section: Discussionmentioning
confidence: 95%
“…In two sporadic cases of OI type IIC termed "dense bone variant", histological examination showed broad, interconnected cartilaginous trabeculae with thin osseous seams in the metaphyses. These cases showed deformed slender long bones with dense metaphyseal margins and normal vertebral bodies which contrasted with the crumpled, thick long bones and multiple vertebral compression fractures in OI IIA [53]. Pace et al have reported as lethal OI, a case in which the ends of long bones were not compressed but had had regions of increased bone density.…”
Section: Sp7/psterixmentioning
confidence: 92%
“…Pace et al reported a COL1A1 4321G-->T transversion in exon 52 that changed a conserved aspartic acid to tyrosine (D1441Y) [54]. In two OI IIC cases reported by Takagi, one sibling had a novel heterozygous mutations in the C-propeptide region of COL1A1, while no mutation in that region was identified in the second patient [53]. In contrast to these type II patients, both COL1A1 and COL1A2 C-propeptide cleavage site mutations were associated with high BMD (DXA) measurements in two subjects reported by Lindhal et al [55] These cases illustrate the lack of genotype/phenotype relationship observed in OI.…”
Section: Col1a1 and Col1a2 Mutations Associated With Type II Osteogenmentioning
confidence: 94%